Séquence d’introduction de discours représenté : faire ou dire ? - Lotfi Abouda; Nina Rendulic (Discours)
In this paper we study a particular use of the verb faire, i.e. as an approximate equivalent of dire introducing a reported speech in French, in a corpus of about one million words, extracted from ESLO (“Sociolinguistic Survey in Orleans”), which consists of samples of recordings carried out 40 years apart (ESLO1 and ESLO2). A first contrastive analysis of the occurrences of reported speech with faire from a micro-diachronic perspective reveals the recent emergence of this structure, mainly in informal interactional genres among young speakers. Alongside the micro-diachronic approach, we conducted a study of reported speech with faire from a synchronic perspective, analyzing its value and variation in an interactional context. We will show that this particular use of faire, which cannot systematically be paraphrased by dire, presents, in relation to the latter, an additional pragmatic value which consists in presentifying a represented speech act by mimicking it and replaying it. This process, along with its rhetorical function of sustaining active listening and involvement by the interlocutor, allows the speaker to conceal an underlying argumentative issue.